Sperm DNA Integrity Test and Assisted Reproductive Technology (Art) Outcome - Violeta Rilcheva; Nina Ayvazova; Lyubomira Ilieva; Svetlana Ivanova; Emiliana Konova (Journal of Biomedical & Clinical Research)
The objective of the study was to investigate the influence of sperm DNA fragmentation index (DFI) by DNA integrity test on pregnancy outcome and pregnancy loss after assisted reproductive technology (ART) procedure: autologous intracytoplasmic sperm injection (ICSI), donation eggs ICSI, and intrauterine insemination (IUI). We investigated men from 531 couples undergoing autologous ICSI procedure (n=416), from couples undergoing donation eggs procedure (n=39) and IUI (n=76). We performed the following interventions: semen analysis, DNA integrity test, embryo scoring by Gardner and Schoolcraft grading system (1999). The study showed no statistically significant differences between the group regarding pregnancy rate (χ2=0.55; p>0.05; OR=1.25, 95% Cl 1.23-1.46; p>0.05). However, with increased levels of DFI, the number of pregnancy losses became higher (including biochemical pregnancies and spontaneous abortions) at OR=5.65 (95% Cl 4.32-7.11; p=0.05). We examined the percentage of grade I blastocysts (by Gardner and Schoolcraft, 1999) before donation eggs embryo transfer and found a statistically significant correlation with both the DFI (χ2=7.80; p